Identification of Novel Cerebrospinal Fluid Biomarkers for Cognitive Decline in Aneurysmal Subarachnoid Hemorrhage: A Proteomic Approach - Liu, Fan; Bao, Yun; Qiu, Binghui; Mao, Jian; Liao, Xixian; Huang, Haorun; Zhang, An; Zhang, Guozhong; Qi, Songtao; Mei, Fen (Frontiers in Cellular Neuroscience, 2022)
Background: Cognitive impairment commonly occurs in aneurysmal subarachnoid hemorrhage (aSAH) survivors. Cerebrospinal fluid (CSF) biomarkers have been proven useful in several central neurological disorders. No such diagnostic biomarkers are available for predicting cognitive impairment after aSAH to date. Here, we aimed to identify novel CSF biomarkers for cognitive deficits after aSAH using an in-depth proteomic approach. Methods: We applied mass spectrometry with data independent acquisition (DIA) quantification to identify biomarker candidates in CSF samples from a well-characterized cohort comprising patients with impaired cognition (n = 9) and patients with intact cognition(n = 9). The potential biological processes and signaling pathways associated with differential proteins were analyzed using R software. The candidates were further validated in a larger independent cohort (n=40) using ELISA. The diagnostic utility of these proteins was investigated by using receiver operating characteristic curve analysis. Results: In total, we identified 628 proteins. The discovery cohort revealed that 115 proteins were differentially expressed in cognitive impairment patients compared to patients with intact cognition(P<0.05). Independent cohort replication confirmed NCAM2, NPTXR, NRXN2, RELN and CNTN2 as sensitive and specific candidate biomarkers for disorders of cognition. Lower CSF levels of all biomarker candidates, except RELN, were associated with more pronounced cognitive decline. Conclusion: We identified and validated five CSF biomarkers for cognitive impairment in aSAH patients. These particular proteins have important predictive and discriminative potential for cognitive impairment in aSAH and could be potential targets for early disease intervention.